Work Measurement Techniques Utilized by The Building Industry in The Midlands Province Of Zimbabwe - Moyo, Tirivavi; Mangore, Ellen; Chigara, Benviolent (International Journal of Sustainable Construction Engineering and Technology, 2014)
The Zimbabwean construction industry, both in the private and public sector, is characterized by cost and time overruns. Whilst the causes are innumerable, labour productivity control, through use of effective work measurement techniques, is paramount as labour constitutes a considerable portion of any construction project. It is therefore expedient that an investigation of the work measurement techniques utilized by the industry be undertaken. Focus was made on the Midlands province, it being resident to a considerable number of mining entities undergoing building construction growth momentum on the back of significant investments since 2009. The survey was undertaken through use of interview administered questionnaires on Construction Industry Federation of Zimbabwe registered companies that are resident in the province and on those that have undertaken or are undertaking construction projects within the same province. Construction companies in the Midlands province have overwhelmingly, albeit inappropriately, used the estimating technique as alluded to by 95% of the respondents. The outputs generated from use of this technique are significantly different from the actual outputs directly causing time overruns on the project sites. The other methods of time study at 33%, work sampling at 10% and synthesis at 5% have been sparingly utilized. The results from the use of time study and work sampling in combination with the estimating technique are within the allowable limits and hence these projects have no time overrun concerns emanating from the use of these techniques.